The Use of Geophysical Prospections to Map Ancient Hydraulic Works: The Triglio Underground Aqueduct (Apulia, Southern Italy). Issue 3 (31st March 2016) - Leucci, Giovanni; Parise, Mario; Sammarco, Mariangela; Scardozzi, Giuseppe
Abstract: This paper presents an integrated analysis using ground‐penetrating radar (GPR) and electrical resistivity tomography (ERT) studies to map the Triglio underground aqueduct that in Roman times supplied fresh water to the ancient town of Tarentum, modern Taranto, Apulia region, Italy. The study area includes an expansion project of a nearby limestone quarry where mining activity is related to the production of a steel factory (ILVA). The aim was to develop methods for detection and mapping of the geometry of the underground aqueduct. Seven GPR reflection profiles were acquired across and parallel to the hypothesized extent of the aqueduct, while the ERT method was used to understand the stratigraphy of the area and tie reflections to geological units. Well‐preserved vertical shafts for ventilation and inspection of the ancient underground hydraulic work were investigated and used as models for GPR exploration. The GPR profiles, interpreted using both the trace amplitude analysis and the forward modelling, showed reflection features from the main horizontal tunnel of the ancient aqueduct. The void space within the aqueduct, usually the ceiling–air interface, was discovered and mapped using reflections profiles both parallel to the linear feature, but also crossing it, and differentiated from similar looking geological features. Copyright © 2016 John Wiley & Sons, Ltd.